The Cocido Madrileno; A Case of Culinary Adhocism - Rios, Alicia (Petits Propos Culinaires, 2024)
This is an edited version of a paper which the author brought with her to the 1984 Oxford Symposium, but which could only be made available to a few of the participants. The author wishes to express her thanks to Manuel Martinez Llopis and Carolo Dorvier ’for their generosity, knowledge, and inspiration’.